Curating Digital Diasporic Intimacies: Black Feminist Approaches to Visual Cultures Online - bruce, keisha (2022)
Through a series of case studies that explore Black women and femmes’ curation of, presence within, and engagement with digital visual cultures, this thesis illustrates how digital diasporic intimacies have been created, shared, and sustained on social media using affective processes of visuality. It brings together cecile emeke’s former YouTube-based web series strolling (2014-16), Renata Cherlise’s Instagram-based archival project @BlackArchives.co, a range of Influencer selfies uploaded onto Instagram with the hashtag #BlackGirlMagic, and a genre of cartoon memes which have been remixed (edited) with Black femme aesthetics, to argue for the importance of visual culture for building diasporic communities and forming diasporic identities on social media. At the centre of this project is the term digital diasporic intimacy, which I use to describe moments of joy, expressions of imagined kinship, and practices of solidarity mediated by the Black diaspora on social media. Focusing on how these visual mediums resonate, create, and engage diasporic intimacies, I consider how tensions, friction, and disagreements expressed on social media also underpin the creation of online communities and can be a practice of diasporic identity negotiation too.